Ignition Parameters of Diesel Layers Under Conditions of Local Heating; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Zakharevich A. V. Arkadiy Vladimirovich; Zygin M. S. Mikhail; Panchenko P. V. Pavel; Vlasova Y. A. Yekaterina (2016, 2016)
Title screen